Structural Evolution and Motion Characteristics of a Hard Roof During Thickening Coal Seam Mining - Zhang, Xiangyang; Zhao, Xiangyang; Luo, Lei (Frontiers in Earth Science, 2022)
This study combined theoretical analysis, physical simulation, and numerical simulation to discuss the influences of the structural evolution and motion characteristics of a hard roof during thickening coal seam mining on working face pressure. Results showed that during the mining of the thickening coal seam with a hard roof, the settlement curve of low-level strata was a stepwise wave slope, and the settlement curve of high-level strata shifted from a “V-shaped” distribution pattern to a parabola under the full mining of the coal seam. When the mining thickness was relatively small, the mining space expanded with the increase in mining thickness due to the “masonry beam” structure formed by the low-level, sub-critical overlying strata. The low-level critical strata formed a “composite cantilever beam” structure with a hard immediate roof after advancing into the caving zone. After complete recovery, the overlying strata were in a steady-movement state, and the plastic failure zone of the overlying strata of the thickening coal seam presented obvious distribution characteristics of longitudinal and transverse partitions. This study provides theoretical reference for coal seam mining under similar geological conditions.